2016
DOI: 10.1002/cjce.22518
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene deposition in a Taylor‐Couette device and a pipe: Theoretically achievable critical deposition regimes

Abstract: In this paper, the effects of major asphaltene deposition model parameters, particle‐particle collision, and particle‐wall sticking efficiencies as well as asphaltene content in a hydrocarbon fluid on asphaltene deposition in both a Taylor‐Couette device and production tubing are numerically studied. The possibility of an increase in asphaltene deposition rate as a result of adding asphaltene inhibitors is investigated. The computations show that this critical effect is achievable in a Taylor‐Couette device op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Asphaltene deposition on metallic surfaces is generally studied using a Taylor–Couette device, capillary tube, , or quartz crystal microbalance with dissipation (QCM-D). , Experiments by Nabzer et al indicated that the asphaltene deposition is diffusion-limited at low shear rates, while no deposition occurred at high shear rates. Eskin and co-workers , studied asphaltene deposition in a Couette device, and they modeled the phenomena by assuming that large particles do not contribute to the deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…Asphaltene deposition on metallic surfaces is generally studied using a Taylor–Couette device, capillary tube, , or quartz crystal microbalance with dissipation (QCM-D). , Experiments by Nabzer et al indicated that the asphaltene deposition is diffusion-limited at low shear rates, while no deposition occurred at high shear rates. Eskin and co-workers , studied asphaltene deposition in a Couette device, and they modeled the phenomena by assuming that large particles do not contribute to the deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have attempted to investigate and measure asphaltene particle size distribution and studied its effects on deposition flux. Eskin et al employed the population balance approach for modeling the evolution of the particle size distribution. ,, According to their experimental data performed in a Couette device, the particle size distribution was very close to a log-normal function. Eskin et al showed that the shear removal rate and, consequently, the total depositing particle flux are influenced by particle size distribution.…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…Modeling results showed that increasing the asphaltene concentration and surface temperature had a tendency to increase the deposition rate of asphaltene; also, the deposition layer thickness is found to increase in the streamwise direction. In other work, Eskin et al studied the effect of asphaltene content and some major model parameters such as particle–particle collision and particle-wall sticking efficiencies on the deposition rate in a Taylor-Couette device and production tubing . Experimental data showed that increasing the asphaltene content leads to enhancing the rate of fluid depletion of particles able to be deposited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, experimental devices allowing the detection of asphaltene deposition on solid surfaces appear to be the most appropriate tools for monitoring asphaltene precipitation and deposition phenomena with and without the presence of a chemical inhibitor. These include the Taylor–Couette device, capillary tube, , and quartz crystal microbalance (QCM). ,,, Additionally, recent progress in scanning tunneling microscopy and atomic force microscopy (AFM) have allowed the visualizing of asphaltene aggregates or asphaltene films on different media and imaging of the atomic structure of complex, polydisperse molecules, including individual asphaltene molecules. AFM has also been used for particle size analysis to characterize how an additive can inhibit the flocculation and/or deposition of asphaltenes on mineral surfaces . While the majority of studies have focused on the effects of carbon dioxide injection on the asphaltene deposition rate during enhanced oil recovery processes, few experimental studies have been conducted to examine the effects of miscible hydrocarbon injection on the asphaltene precipitation. , In particular, when natural gas is preferred to CO 2 in deep high-pressure reservoirs with high permeability, it is important to test the performance of chemical inhibitors to prevent the destabilization and deposition of asphaltenes over a wide range of temperature and pressure conditions during oil production.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, experimental devices allowing the detection of asphaltene deposition on solid surfaces appear to be the most appropriate tools for monitoring asphaltene precipitation and deposition phenomena with and without the presence of a chemical inhibitor. These include the Taylor−Couette device, 34 capillary tube, 35,36 and quartz crystal microbalance (QCM). 8,9,37,38 Additionally, recent progress in scanning tunneling microscopy and atomic force microscopy (AFM) have allowed the visualizing of asphaltene aggregates or asphaltene films on different media 39−42 and imaging of the atomic structure of complex, polydisperse molecules, including individual asphaltene molecules.…”
Section: Introductionmentioning
confidence: 99%